Rice in Deep Water - Catling, David. author. aut Link
XXI, 542 p.
Keywords: Rice in Deep Water gives a detailed description of the complex agroecosystem and the growth and development of deepwater rice, a fascinating crop grown by subsistence farmers in the deltas and floodplains of Asia and West Africa flooding to depths of 2-3 metres. An account of the various cultural methods and socioeconomic conditions of the farmers is given, current research efforts to increase productivity discussed and research priorities suggested. The book is designed and profusely illustrated so as to emphasize the complexity and dynamic nature of plant and environment, an aspect so often poorly appreciated and misunderstood.